2012
DOI: 10.1007/s00432-012-1192-4
|View full text |Cite
|
Sign up to set email alerts
|

The bodies fight against cancer: is human leucocyte antigen (HLA) class 1 the key?

Abstract: Variability in antibody use makes it difficult to validate HLA class I expression as an independent prognostic marker in GI cancer. Consensus guidelines, incorporating heavy and light chain antibodies, are required with further studies on HLA class I expression being performed to validate its prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…[12][13][14] Accordingly, expression status of HLA class I molecules on tumor cells may influence prognosis, and several clinical studies showed that downregulation or low expression of HLA class I antigens was associated with a poor prognosis in a variety of malignant tumors, including NSCLC. 17,[34][35][36] PD-L1, expressing on tumor cells, also plays an important role in immune evasion at the final step by inhibiting activated CTLs. Accordingly, tumor cells with reduced HLA class I expression may evade immune attack regardless of PD-L1 expression on tumor cells, which may account for the lack of prognostic impact of PD-L1 status in tumors with reduced HLA class I expression found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Accordingly, expression status of HLA class I molecules on tumor cells may influence prognosis, and several clinical studies showed that downregulation or low expression of HLA class I antigens was associated with a poor prognosis in a variety of malignant tumors, including NSCLC. 17,[34][35][36] PD-L1, expressing on tumor cells, also plays an important role in immune evasion at the final step by inhibiting activated CTLs. Accordingly, tumor cells with reduced HLA class I expression may evade immune attack regardless of PD-L1 expression on tumor cells, which may account for the lack of prognostic impact of PD-L1 status in tumors with reduced HLA class I expression found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue sections were stained according to the previously described protocol [ 9 ]. Sections were incubated at room temperature over night with mouse monoclonal antibodies HCA2 and HC10 (anti-HLA-A and anti-HLAB/C, respectively) [ 9 , 23 ] for the detection of classical HLA class I on the tumor cell surface. Non-classical HLA class I staining was performed using mouse monoclonal antibodies against HLA-E (MEM-E/02 Clone (sc-51621, Santa Cruz biotechnology, Dallas, Texas) and HLA-G (4H84 Clone (sc-21799, Santa Cruz Biotechnology, Dallas, Texas) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have reported that both the TME, including the TILs, macrophages, and immune-checkpoint molecules, and clinicopathologic features influence cancer prognosis. [6][7][8][9][10] In CRC, a high number of TILs are associated with better prognosis, 6,7 and the expression of some immune-checkpoint molecules can be useful prognostic biomarkers. 8,9,[11][12][13] However, it remains unclear whether immunity differs according to the tumor location and which cells or molecules are involved in cancer prognosis.…”
Section: Introductionmentioning
confidence: 99%